Thermodynamics of mixing of the -adrenergic blocker propranolol-hcl in ethanol + water mixtures (2011)
Thermodynamic functions Gibbs energy, enthalpy, and entropy of mixing of propranolol hydrochloride in ethanol + water mixtures were evaluated. Mixing quantities were calculated based on fusion calorimetric values obtained from differential scanning calorimetry measurements and equilibrium solubility values reported in the literature for this drug in these cosolvent mixtures. By means of enthalpy-entropy compensation analysis, a non-linear ∆ mix H° vs. ∆ G° plot was obtained indicating different mechanisms involved in the dissolution and mixing of this drug according to mixtures composition. Nevertheless, the molecular and ionic events involved in the dissolution of this drug in this cosolvent system are unclear.